Avoidant/restrictive food intake disorder: A systematic scoping review of the current literature. (June 2020) - Bourne, Laura; Bryant-Waugh, Rachel; Cook, Julia; Mandy, William
Highlights: This review provides the first full systematic outline of the ARFID literature. Though evidenced as a distinct clinical entity, there are pressing knowledge gaps. Four areas of focus for ARFID research in the next five years are proposed. Of particular importance is the need to better characterise its varied presentation. Abstract: Avoidant/restrictive food intake disorder (ARFID) was recently introduced to psychiatric nosology to describe a group of patients who have avoidant or restrictive eating behaviours that are not motivated by a body image disturbance or a desire to be thinner. This scoping review aimed to systematically assess the extent and nature of the ARFID literature, to identify gaps in current understanding, and to make recommendations for further study. Following an extensive database search, 291 unique references were identified. When matched against pre-determined eligibility criteria, 78 full-text publications from 14 countries were found to report primary, empirical data relating to ARFID. This literature was synthesised and categorised into five subject areas according to the central area of focus: diagnosis and assessment, clinical characteristics, treatment interventions, clinical outcomes, and prevalence. The current evidence base supports ARFID as a distinct clinical entity, but there is a limited understanding in all areas. Several possible avenues for further study are indicated, with an emphasis placed on first parsing this disorder's heterogeneous presentation. A better understanding of the varied mechanisms which drive food avoidance and/or restriction will inform the development of targeted treatment interventions, refine screening tools and impact clinical outcomes.